What are the symptoms of internal rectal prolapse?. (27th February 2013) - Wijffels, N. A. T.; Jones, O. M.; Cunningham, C.; Bemelman, W. A.; Lindsey, I.
Abstract Aim Although high‐grade internal rectal prolapse is believed to cause functional symptoms such as obstructed defaecation, little has been published on the exact distribution and frequency of symptoms. The aim of this study was to identify the most common symptoms of patients with high‐grade internal rectal prolapse. Method Patients were diagnosed with high‐grade prolapse (grade 3 and 4) on proctography using the Oxford Rectal Prolapse Grade. Information from a prospectively collected database was supplemented by a retrospective case note review. Results Eighty eight patients (94% of them women) were included for analysis. Faecal incontinence (56%) was the most common symptom at presentation. Symptoms related to obstructed defaecation syndrome were the next most common, including incomplete evacuation (45%), straining (34%), digital assistance (34%) and repetitive toilet visits (33%). Conclusion A variety of symptoms may be caused by high‐grade internal rectal prolapse Although symptoms of obstructed defaecation were frequent, urge faecal incontinence was the most common.